Política.com - partidos políticos e websites: estudo comparado entre Brasil e Argentina - Santos, Jaqueline Aparecida Alves dos (2013)
The objective of this study is to conduct a comparative analysis of qualitative character of the constituent elements of the websites of political parties in Brazil and Argentina. They are: Brazilian Democratic Movement Party ( PMDB ), the Workers Party ( PT) , Communist Party of Brazil ( PC do B ) ; Christian Social Democratic Party ( CSDP ) ; Unión Civica Radical ( UCR ), the Justicialist Party ( PJ ), Socialist Party Argentino ( PS ) and the Communist Party of Argentina ( PCA ) . It is intended to verify that the strand ideological and organizational structure Subtitle influence the manner of use of the websites, thus establishing different forms of use of this feature. It is considered that in addition to the internal features of each party, the general aspects of modern parties, while bureaucratic organizations are important to understand their behavior in the virtual world . The analysis proceeds with an initial characterization of layouts , followed by the description and analysis of the resources available on websites , grouped into four categories : ( i ) information about the party , whose purpose was to verify claims by Subtitle to disseminate information to users about their identity and organization , (ii ) recruitment; whose aim was to analyze the resources used to recruit voters individually or by groups, as well as advertising materials and training schools policy , ( iii ) transparency and accountability ; observed the presence of resources and documents that demonstrate transparency in administration and ( iv ) interaction and participation was analyzed the means employed to generate political interest and interaction with the web user . Also raised were the main features of the news released by the parties. All these analyzes point to the general conclusion that the websites are used by all parties as a communication tool unilateral policy. Identified some differences in layout and content focus by some parties with similar characteristics , however, it was found that the slope ideological and organizational structure of the subtitles do not determine one expressively different usage , for arguing that certain type of party tends to use the site differently from another party . Although the hypothesis was not confirmed, the idea that guided the work was not entirely refuted because it was possible to observe these spaces general characteristics of modern parties, the liberal perspective systemized.